MEMBERDAYAKAN MASYARAKAT DALAM PENGELOLAAN SAMPAH BERKELANJUTAN - Lena Ahdiani Hayati (Universitas Islam Al-Ihya Kuningan, 2024)
The waste problem in Indonesia has reached an alarming level, with national waste production reaching 67.8 million tons per year. This article examines the community empowerment approach as an alternative solution in sustainable waste management. Through literature analysis and case studies, this study explores implementation strategies, program successes, challenges faced, and formulates policy recommendations. The results of the study indicate that community empowerment, through initiatives such as waste banks and community-based recycling programs, has significant potential in reducing waste volume, increasing environmental awareness, and creating economic value from waste. However, challenges such as resistance to change, limited resources, and program sustainability issues still need to be addressed. This study concludes that the success of community empowerment in waste management requires a holistic approach, involving strengthening regulations, increasing institutional capacity, and solid multi-stakeholder partnerships